Perforation rate in CT colonography: a systematic review of the literature and meta-analysis - Bellini, Davide; Rengo, Marco; De Cecco, Carlo Nicola; Iafrate, Franco; Hassan, Cesare; Laghi, Andrea (European radiology, 2014)
Purpose The primary aim was to assess the perforation rate of CTC; the secondary aim was to identify potential clinical/technical predictors of this complication. Methods Methods for analysis were based on PRISMA (preferred reporting items for systematic reviews and meta-analyses). From the selected studies, the rate of CTC perforation and patient/technical characteristics potentially associated with this event were extracted. Forest plots showing individual and pooled estimates of the perforation rate were obtained for all analyses. I 2 was used to evaluate heterogeneity between studies. Results Eleven articles out of the 187 initially identified were selected for the analysis (103,399 patients). There were 29,048 (28 %) asymptomatic individuals and 30,773 (30 %) symptomatic patients; this characteristic was not reported in the remaining subjects (42 %). Colon distension was obtained manually in 69,222 (67 %) and using an automated carbon dioxide insufflator in 26,479 (26 %) patients; in the remaining 7 % of patients, this information was missing. Twenty-eight colonic perforations were reported, with the CTC perforation rate estimated to be 0.04 % (95 % CI. 0.00-0.10), 19-fold higher in symptomatic than in screening subjects (OR: 19.2, CI 3.3-108 and P = 0.001). The surgical rate was 0.008 %. No CTC-related deaths were reported. Conclusions The perforation rate in CTC is very low, particularly considering asymptomatic individuals. Key Points • This is the first meta-analysis on this topic, based on 100,000 patients . • The CTC-related colorectal perforation rate is 0.04 %, 0.02 % in asymptomatic subjects . • The CTC-induced surgery rate is 0.008 % (1:12,500) . • The perforation rate in CTC is low, particularly in average-risk, asymptomatic individuals .